2018
DOI: 10.12669/pjms.346.15962
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification in the anterior chamber: An alternative surgical technique in post-vitrectomy cataract

Abstract: Objective:To evaluate the characteristics, safety and effectiveness of a modified technique of phacoemulsification in post-vitrectomy cataracts.Methods:This retrospective clinical trial comprised 31 patients (31 eyes) with post-vitrectomy cataract, who had undergone phacoemulsification combined with intraocular lens implantation. An alternative surgical technique known as phacoemulsification in the anterior chamber was used for nucleus management in those cases. The following parameters were evaluated: best co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…A similar technique was reported by Yu et al, who recommended phacoemulsi cation in the anterior chamber for post-vitrectomy cataract. 10 In conclusion, the results of our study are encouraging that the prechop technique was found to have less intraoperative complications, reduced phaco time and CDE compared to standardized phaco-chop during cataract phacoemulsi cation surgery. It might be a good alternative for cataract surgery for patients with highly lique ed vitreous, such as in high myopia-related and post-vitrectomy cataract, especially those with hard nucleus.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…A similar technique was reported by Yu et al, who recommended phacoemulsi cation in the anterior chamber for post-vitrectomy cataract. 10 In conclusion, the results of our study are encouraging that the prechop technique was found to have less intraoperative complications, reduced phaco time and CDE compared to standardized phaco-chop during cataract phacoemulsi cation surgery. It might be a good alternative for cataract surgery for patients with highly lique ed vitreous, such as in high myopia-related and post-vitrectomy cataract, especially those with hard nucleus.…”
Section: Discussionsupporting
confidence: 57%
“…Cataract surgery in patients with highly lique ed or vitrectomized vitreous is challenging due to its unique anatomical structures. To solve this problem, previous researchers, such as Li et al 5 and Yu et al 10 has reported modi ed methods which had certain effectiveness in improving the safety of surgery and reducing complications, but there are still some limitation for their methods. In the current study, we reported with encouraging results that prechop technique had an advantage in treating patients with highly lique ed vitreous compared to conventional phaco chop during cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the height of irrigating fluid is kept excessively low, the Phaco cannot proceed efficiently. Yu et al 9 have tried rotating the nucleus from the capsular bag to the anterior chamber for Phaco to reduce the pressure on the posterior capsule. However, this method can cause endothelial cell loss, an inflammatory response in the anterior chamber, and corneal edema, moreover it also does not resolve the issue of reverse pupillary block as well.…”
Section: Discussionmentioning
confidence: 99%
“…Для предотвращения сужения зрачка и поддержания необходимого мидриаза на протяжении всей операции было предложено вводить в переднюю камеру раствор адреналина или использовать ирис-ретракторы [6]. Tau Yu et al (2018) сообщили, что увеличенная глубина передней камеры на фоне авитрии позволяет производить удаление хрусталика в передней камере, поддерживая безопасное расстояние до эндотелия роговицы и уменьшая риск повреждения задней капсулы [24]. Таким образом, применение вышеуказанных технических приемов позволяет избежать специфических осложнений, характерных для ФЭК, на авитреальных глазах и обосновывает выполнение ФЭК в качестве альтернативной хирургии второго этапа после ВРХ при реабилитации пациентов с ПДР.…”
unclassified